Transient response of a ship to an abrupt flooding accounting for the momentum flux. (August 2015) - Manderbacka, Teemu; Mikkola, Tommi; Ruponen, Pekka; Matusiak, Jerzy
Abstract: Numerical non-linear time domain simulation method for damaged ship motions is presented. Floodwater motion modelling is based on the lumped mass method with a moving free surface. The ship and floodwater motions are fully coupled. The variation of the floodwater mass is accounted for. A model to account for the flooding ingress transporting the momentum is presented. The experiments of abrupt flooding have shown that the ship may experience the first large roll towards the undamaged side, especially when a large undivided compartment is flooded. The presented time domain model is validated against the experimental data on the roll damping of the flooded ship and transient flooding. Two different initial stability conditions and two different compartment layouts are studied. Viscous dissipation of the floodwater motions is modelled with an equivalent friction coefficient. The impact of the viscous damping is studied. Transient flooding tests show that the inflow momentum has to be accounted for when the undivided compartment is flooded. The simulation model is capable of capturing the impact of the inflooding jet and the first roll on the opposite side of the damage is reproduced. Abstract : Highlights: Flooded water and damaged ship dynamics are fully coupled. Mass variation and transfer of momentum in flooding is accounted for. Calculation time-wise effective numerical time domain simulation tool is presented. Simulation tool is validated against the model experiment data.